Correlating keratin solution behaviour to the physical properties of resulting electrospun matrices - Sendy Agung Purnomo (2014)
Keratin emerges as an attractive protein of human origin to be used as a template for tissue regeneration because it can be easily extracted from the unlimited supply of human hair, making it abundant and readily available. In addition, interest in electrospinning has recently escalated as it is an inexpensive and simple technique to fabricate nanofibrous scaffolds that are able to mimic the extracellular matrix (ECM) to facilitate cell adhesion and proliferation during tissue regeneration processes. Hence, in this study, we explored the possibility of electrospinning keratin-based scaffolds for tissue regeneration application. Pure keratin, by itself, is not able to be electrospun into nanofibrous scaffolds due to its low molecular weight. Hence, to facilitate the electrospinning of keratin, polyethylene oxide (PEO) was added into the electrospinning solution. A variety of concentrations and keratin: PEO formulations were electrospun and it was found that 30wt% keratin and 0.5wt% PEO resulted in the formation of fibers with good morphology and minimal bead defects. The upper and lower limits of suitable viscosity for electrospinning of keratin – PEO system were determined to be 21.8 mPas and 36.3 mPas, respectively. This formulation was then used for downstream characterisations and studies. For downstream studies, attempts to produce highly aligned fibers that have better cell adhesion and proliferation properties than random fibers were done by varying the controlling parameters in the electrospinning setup. The results showed that the optimised combination of parameters to get such aligned fibers were: (1) at 10kV applied voltage, 15cm distance, 0.5ml/h feed rate and 500rpm drum speed or (2) at 15kV applied voltage, 15cm distance, 0.5 ml/h feed rate and 600rpm drum speed. The dependence of the physical properties of the resulting fibers with individual controlling parameters were also examined in this study. The samples were then characterized for its degradation profile as biodegradation is an important material property for tissue regeneration application. This was done by using deionised H2O for hydrolysis test, followed by chymotrypsin and proteinase-K for enzymatic digestion test. Results showed that proteinase-K digested keratin more effectively than chymotrypsin. Overall, this project has successfully correlated the keratin solution behaviour to the physical properties of resulting electrospun matrices, but future researches could be done to further characterise these fibers, in terms of mechanical properties and cell compliances.